Determinants of Neonatal seizure among newborns attending a tertiary care Hospital - Ara, Rowshan; Uddin, Md Nasir (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Neonatal seizure is an important cause of childhood mortality and morbidity. The prevalence of neonatal seizure is 2-3 /1000 live births in term and 10-15 /1000 preterm deliveries in our country. Proper neonatal care is crucial. Different study results representing the risk factors for neonatal seizure are directly and indirectly related. Objectives: The study was carried out to determine the factors influencing neonatal seizure among the patients attending a tertiary care hospital. Methods: A cross- sectional study was carried out to find out the factors of neonatal seizure where face to face interview was taken to 50 purposively selected respondents who were attending a tertiary care hospital during spring season. All the data were entered into a personal computer and thoroughly checked for any possible errors and then processed and analyzed by statistical Package for Social Science (SPSS) version 17 and MS office 2007. Results: Among the total respondents mostly were of <25 years (Mean±Sd, 23.16 ±3.919) of age. 36% had primary level education and 32% were illiterate. The mean monthly family income was 11392.0 ±11551.81 BDT. Respondents by pregnancy related complications were mostly of Pre-Eclamptic Toxemias (PET) in 22% cases and anaemia in 24% cases. Gestational age of the respondents was mainly >37weeks.The study also reported that antenatal care by doctors was taken in 64% cases. Among the delivery related factors, most of the deliveries took place at home (64%). Among the neonatal factors weight <2kg was found in 34% cases and 2.1-2.4 kg in 56% cases respectively. 85 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Study also reported that the causes of seizures were Peri-natal Asphyxia (PNA) (12%) and LBW (11%). Respondents by onset of seizure were mostly within 24 hours (44%), common types of seizure were subtle (50%) and duration of seizures was found to be less than 5 min in (64%) cases. The study also revealed the association between the causes and types of seizure; the result showed that 60% of subtle type of seizure was associated with Infant of Diabetic Mother (IDM) followed by focal type (40%). PNA was associated with 58% of subtle type of seizure. Our result was found statistically insignificant (p>0.05). Association of onset of seizure and birth weight of the neonates also revealed insignificant (p>0.05) result. This can be explained by small sample size and short duration of study. On the other hand other studies reported significant (p<0.05) results as they had larger sample size and longer study period. Conclusion: Maternal factors, neonatal factors and delivery related factors are related to neonatal seizure. Further studies involving larger sample size is recommended. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22931 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014